Thermally conductive sheet and method for producing same

The thermal conducting sheet, featuring a crosslinked resin and particulate filler with enhanced thermal conductivity and sheet strength, addresses the issue of tearing under pressure, ensuring durability and preventing short circuits in electronic devices.

JP7669644B2Active Publication Date: 2025-04-30ZEON CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020058963
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-03-27
Publication Date
2025-04-30
Estimated Expiration
2040-03-27

AI Technical Summary

Technical Problem

Conventional thermal conducting sheets are prone to tearing when used under pressure, leading to potential short circuits in electronic devices.

Method used

A thermal conducting sheet with a crosslinked resin and particulate filler, having a thermal conductivity of 12 W/m·K or more in the thickness direction, and a sheet strength in the main in-plane direction Y of 1.0 N/mm² or more, along with a controlled number of micropores, is developed.

Benefits of technology

The sheet is difficult to tear when used, ensuring durability and preventing short circuits in electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669644000001
    Figure 0007669644000001
Patent Text Reader

Abstract

To provide a heat-conductive sheet which is less likely to be torn off during usage.SOLUTION: A heat-conductive sheet contains a resin and a particulate filler, and has heat conductivity in a thickness direction of 12 W / m K or more, in which the resin contains a crosslinked resin, and in measurement of a sheet strength on a main surface of the heat-conductive sheet, a sheet strength in a main in-plane direction Y vertical to a main in-plane direction X with the highest sheet strength is 1.0 N / mm2 or more, and the number of micropores that penetrate through the heat-conductive sheet in a thickness direction and have a pore diameter of 48 μm or more and 500 μm or less is 200 pieces or less per 1 cm2 of an area of the heat-conductive sheet in plan view.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermally conductive sheet and a method for producing the same. [Background technology]

[0002] In recent years, the amount of heat generated by electronic components such as power semiconductors (e.g., IGBT modules) and integrated circuit (IC) chips has increased as their performance has improved. As a result, it has become necessary to take measures to prevent malfunctions caused by temperature rises in electronic devices that use these components.

[0003] As a countermeasure against functional failures caused by temperature rises in electronic components, a method is generally adopted in which a heat sink, heat sink plate, heat sink fin, or other heat sink made of metal is attached to the heat generating body of the electronic component to promote heat dissipation. When using a heat sink, in order to efficiently transfer heat from the heat generating body to the heat sink, a sheet-like member with high thermal conductivity (thermal conductive sheet) is placed between the heat generating body and the heat sink, and a certain pressure is applied to the thermal conductive sheet to bring the heat generating body and the heat sink into close contact with each other.

[0004] In order to increase the thermal conductivity in the thickness direction, the thermally conductive sheet can be produced, for example, by pressure molding a composition containing a resin and a particulate filler, stacking the resulting sheet-like molded body in the thickness direction, or folding or rolling the sheet to form a laminate, and then slicing the laminate. In the thermally conductive sheet manufactured by slicing the laminate in this manner, it is required to ensure that the sheet strength is sufficiently high. In a thermally conductive sheet produced by slicing a laminate, it is relatively easy to improve the sheet strength in the principal in-plane direction X (direction perpendicular to the stacking direction of the laminate) in which the thermal conductivity is highest when the thermal conductivity is measured on the main surface of the thermally conductive sheet, but it is difficult to improve the sheet strength in the principal in-plane direction Y (direction coinciding with the stacking direction of the laminate) perpendicular to the principal in-plane direction X.

[0005] Patent Document 1 discloses a thermally conductive sheet obtained by slicing a laminate at a predetermined angle, in which the sheet strength in the main in-plane direction X and the sheet strength in the main in-plane direction Y are made uniform by slicing the laminate at a predetermined angle. Patent Document 2 discloses a heat transfer sheet in which a metal vapor deposition film is provided on one surface of a base sheet containing a binder component and anisotropic graphite powder, the anisotropic graphite powder being oriented in the thickness direction. By providing the metal vapor deposition film, the sheet strength of the heat transfer sheet is improved. Moreover, Patent Document 3 discloses that a crosslinking reaction is caused while a laminate is pressurized in the lamination direction. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 6156337 [Patent Document 2] Patent No. 5678596 [Patent Document 3] Patent No. 5423455 Summary of the Invention [Problem to be solved by the invention]

[0007] When the thermally conductive sheet is used in a heated state by being sandwiched between a heat generating body and a heat sink, repeated cycles of pressure and decompression can cause the thermally conductive sheet to tear at the portion to which strong pressure is applied, and the sheet can protrude from between the heat generating body and the heat sink. Because protruding thermally conductive sheets can cause short circuits in electronic devices, thermally conductive sheets are required to be resistant to tearing during use.

[0008] However, the thermally conductive sheets of the above-mentioned conventional techniques have room for improvement in terms of resistance to tearing during use.

[0009] Therefore, an object of the present invention is to provide a thermally conductive sheet that is not easily torn during use. [Means for solving the problem]

[0010] The present inventors have conducted extensive research to achieve the above object, and have found that in a thermally conductive sheet that includes a resin containing a crosslinked resin and a particulate filler and has a thermal conductivity in the thickness direction of a predetermined value or more, if the sheet strength in the main in-plane direction Y perpendicular to the main in-plane direction X in which the sheet strength is highest is set to a predetermined value or more and the number of predetermined micropores is set to a predetermined value or less, the thermally conductive sheet is less likely to tear during use, and have completed the present invention.

[0011] That is, the present invention has an object to advantageously solve the above-mentioned problems, and provides a thermally conductive sheet comprising a resin and a particulate filler, and having a thermal conductivity in a thickness direction of 12 W / m K or more, wherein the resin contains a crosslinked resin, and in a measurement of the sheet strength of a main surface of the thermally conductive sheet, the sheet strength in a main in-plane direction Y perpendicular to a main in-plane direction X in which the sheet strength is highest is 1.0 N / mm 2 or more, and the number of micropores penetrating the thermal conductive sheet in the thickness direction and having a pore size of 48 μm or more and 500 μm or less is equal to or greater than 1 cm2 of the planar area of ​​the thermal conductive sheet. 2 In this way, a thermally conductive sheet that contains a resin containing a crosslinked resin and a particulate filler, has a thermal conductivity in the thickness direction equal to or greater than a predetermined value, and in measurement of the sheet strength of the main surface, has a sheet strength in the main in-plane direction Y perpendicular to the main in-plane direction X in which the sheet strength is highest equal to or greater than a predetermined value, and has a number of predetermined micropores equal to or less than a predetermined value, is unlikely to tear during use. In the present invention, "thermal conductivity," "sheet strength," and "the number of micropores that penetrate the thermal conductive sheet in the thickness direction and have a pore diameter of 48 μm or more and 500 μm or less" can be measured by the method described in the examples of this specification.

[0012] Here, in the thermal conductive sheet of the present invention, it is preferable that the crosslinked resin is a solid at room temperature and normal pressure, and the resin further contains a resin that is a liquid at room temperature and normal pressure. By using a crosslinked resin that is a solid at room temperature and normal pressure in combination with a resin that is a liquid at room temperature and normal pressure, the flexibility of the thermal conductive sheet can be increased.

[0013] In the thermally conductive sheet of the present invention, the volume ratio of the particulate filler to the total volume of the resin and the particulate filler is preferably 30% by volume or more. If the volume ratio of the particulate filler to the total volume of the resin and the particulate filler is 30% by volume or more, the thermally conductive sheet is more resistant to tearing during use and has higher thermal conductivity.

[0014] Furthermore, the thermally conductive sheet of the present invention preferably has a surface roughness Sa of 2.4 μm or less. If the surface roughness Sa is equal to or less than the above-mentioned predetermined value, the thermally conductive sheet can be made more resistant to tearing during use. In the present invention, the surface roughness Sa of the thermal conductive sheet can be measured by the method described in the examples of this specification.

[0015] The present invention also aims to advantageously solve the above-mentioned problems, and the method for producing a thermally conductive sheet of the present invention includes a pre-thermally conductive sheet forming step of pressurizing a composition containing a resin containing a crosslinkable resin, a particulate filler, and a crosslinking agent to form it into a sheet to obtain a pre-thermally conductive sheet, a laminate formation step of stacking a plurality of the pre-thermally conductive sheets in the thickness direction or folding or rolling the pre-thermally conductive sheet to obtain a laminate, a crosslinking reaction step of heating the laminate while pressurizing it in the stacking direction to cause a crosslinking reaction, and a slicing step of slicing the laminate at an angle of 45° or less with respect to the stacking direction to obtain a thermally conductive sheet, and is characterized in that it satisfies at least one of the following (1) to (3): (1) The content of the crosslinkable resin in the resin is 70 mass % or less. (2) The ratio of the volume of the particulate filler to the total volume of the resin and the particulate filler is 30 volume % or more. (3) The heating temperature in the crosslinking reaction step is 150° C. or lower. According to the method for producing a thermally conductive sheet of the present invention, it is possible to produce a thermally conductive sheet that is difficult to tear during use.

[0016] Here, in the method for producing a thermally conductive sheet of the present invention, the pressure applied to the laminate in the lamination direction in the crosslinking reaction step is preferably 0.01 MPa or more. If the pressure applied to the laminate in the lamination direction in the crosslinking reaction step is equal to or more than the above-mentioned predetermined value, the thermally conductive sheet can be made more resistant to tearing during use.

[0017] The method for producing a thermal conductive sheet of the present invention further comprises the steps of: the composition comprises an initiator; The above Reaction initiator It is preferred that the solvent contains dibenzoyl peroxide. The composition includes an initiator, If the thermal conductive sheet contains dibenzoyl peroxide, it can be made even more difficult to tear during use. Effect of the Invention

[0018] According to the present invention, it is possible to provide a thermally conductive sheet that is not easily torn during use. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, an embodiment of the present invention will be described in detail. Since the thermally conductive sheet of the present invention has thermal conductivity, it can be used by being sandwiched between a heat generating body and a heat dissipating body. That is, the thermally conductive sheet of the present invention can be used as a heat dissipating member to constitute a heat dissipating device together with a heat dissipating body such as a heat sink, a heat dissipating plate, or a heat dissipating fin. The thermally conductive sheet of the present invention can be efficiently manufactured using, but is not limited to, a manufacturing method for a thermally conductive sheet of the present invention, which will be described later.

[0020] (Thermal Conduction Sheet) The thermally conductive sheet of the present invention contains a resin and a particulate filler. The thermally conductive sheet of the present invention may further contain optional components other than the resin and the particulate filler. The thermally conductive sheet of the present invention has a thermal conductivity in the thickness direction of 12 W / m·K or more. The thermally conductive sheet of the present invention has a resin containing a crosslinked resin, and in a measurement of the sheet strength of the main surface of the thermally conductive sheet, the sheet strength in the main in-plane direction Y perpendicular to the main in-plane direction X in which the sheet strength is highest is 1.0 N / mm or more, and the number of micropores that penetrate the thermally conductive sheet in the thickness direction and have a pore size of 48 μm or more and 500 μm or less is 1.0 N / mm or more per cm of the planar area of ​​the thermally conductive sheet. 2 It is characterized in that there are 200 or less per unit area. The thermal conductive sheet of the present invention contains a resin that contains a crosslinked resin, has a sheet strength in a predetermined in-plane direction Y of a predetermined value or more, and has a predetermined number of micropores that are each 1 cm2 in plan view area. 2 Since the contact is equal to or less than a predetermined value, the thermal conductive sheet of the present invention is unlikely to tear even during use. For example, even if the thermal conductive sheet of the present invention is sandwiched between a heat generating body and a heat dissipating body and heated, and is subjected to repeated cycles of pressure and pressure reduction, the thermal conductive sheet of the present invention is unlikely to tear. Therefore, the thermal conductive sheet of the present invention has excellent durability.

[0021] <Resin> The heat conductive sheet of the present invention contains a resin, so that the heat generating body and the heat dissipating body can be well adhered to each other via the heat conductive sheet. In this specification, rubber and elastomer are included in the "resin". The resin that may be contained in the thermally conductive sheet of the present invention constitutes a matrix resin and also functions as a binder that binds the particulate filler. The resin contained in the thermal conductive sheet of the present invention contains a crosslinked resin, and optionally contains a resin other than the crosslinked resin (other resin).

[0022] <<Crosslinked resin>> The resin contained in the thermal conductive sheet of the present invention contains a cross-linked resin. The cross-linked resin is a resin cross-linked by a cross-linking agent. The thermal conductive sheet of the present invention contains a cross-linked resin as a resin, so that the sheet strength can be ensured to be sufficiently high, and the sheet is less likely to tear during use.

[0023] Here, the crosslinked resin is usually solid at room temperature and normal pressure. In this specification, "room temperature" refers to 23° C., and "normal pressure" refers to 1 atm (absolute pressure).

[0024] The crosslinked resin is formed by crosslinking the crosslinkable resin with the crosslinking agent. In the crosslinking reaction, a reaction initiator can be used. The crosslinking reaction is not particularly limited, but for example, a peroxide crosslinking reaction in which a reaction is carried out in the presence of an organic peroxide as a reaction initiator can be used.

[0025] [Crosslinkable resin] The crosslinkable resin is not particularly limited, but for example, a crosslinkable resin capable of reacting with a crosslinking agent by a peroxide crosslinking reaction can be used. As the crosslinkable resin, for example, a resin that is solid at room temperature and normal pressure can be used, although this depends on the types of crosslinking agent and reaction initiator (that is, the type of crosslinking reaction).

[0026] - A resin that is solid at room temperature and pressure - As the resin that is solid at room temperature and normal pressure, for example, a thermoplastic resin that is solid at room temperature and normal pressure can be used.

[0027] --Thermoplastic resin that is solid at room temperature and pressure-- Examples of thermoplastic resins that are solid at room temperature and pressure include acrylic resins such as poly(2-ethylhexyl acrylate), copolymers of acrylic acid and 2-ethylhexyl acrylate, polymethacrylic acid or its ester, and polyacrylic acid or its ester; silicone resins; fluororesins; polyethylene; polypropylene; ethylene-propylene copolymers; polymethylpentene; polyvinyl chloride; polyvinylidene chloride; polyvinyl acetate; ethylene-vinyl acetate copolymers; polyvinyl alcohol; polyacetal; polyethylene terephthalate; polybutylene terephthalate; polyethylene naphthalate; polystyrene. Examples of the polyphenylene include styrene, polyacrylonitrile, styrene-acrylonitrile copolymer, acrylonitrile-butadiene-styrene copolymer (ABS resin), styrene-butadiene block copolymer or hydrogenated product thereof, styrene-isoprene block copolymer or hydrogenated product thereof, polyphenylene ether, modified polyphenylene ether, aliphatic polyamides, aromatic polyamides, polyamideimide, polycarbonate, polyphenylene sulfide, polysulfone, polyethersulfone, polyethernitrile, polyetherketone, polyketone, polyurethane, liquid crystal polymer, ionomer, etc. These may be used alone or in combination of two or more in any ratio. Among these, from the viewpoint of improving the flame retardancy, heat resistance, oil resistance, chemical resistance, etc. of the thermal conductive sheet, it is preferable that the thermoplastic resin that is solid at room temperature and normal pressure is a thermoplastic fluororesin that is solid at room temperature and normal pressure.

[0028] = Thermoplastic fluororesin that is solid at room temperature and pressure = The thermoplastic fluororesin that is solid under normal temperature and normal pressure is not particularly limited as long as it is a thermoplastic fluororesin that is solid under normal temperature and normal pressure. Examples of the thermoplastic fluororesin that is solid under normal temperature and normal pressure include elastomers obtained by polymerizing fluorine-containing monomers, such as vinylidene fluoride-based fluororesin, tetrafluoroethylene-propylene-based fluororesin, and tetrafluoroethylene-purple vinyl ether-based fluororesin. More specifically, polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-ethylene copolymer, polyvinylidene fluoride, polychlorotrifluoroethylene, ethylene-chlorofluoroethylene copolymer, tetrafluoroethylene-perfluorodioxole copolymer, polyvinyl fluoride, tetrafluoroethylene-propylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer, acrylic modified polytetrafluoroethylene, ester modified polytetrafluoroethylene, epoxy modified polytetrafluoroethylene, and silane modified polytetrafluoroethylene can be mentioned. These may be used alone or in any ratio of two or more. Among these, from the viewpoint of processability, polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer, and acrylic modified polytetrafluoroethylene are preferred.

[0029] In addition, examples of commercially available thermoplastic fluororesins (fluoroelastomers (fluororubbers)) that are solid at room temperature and normal pressure include Dai-el (registered trademark) G-912, G-700 series, Dai-el G-550 series / G-600 series, and Dai-el G-310 manufactured by Daikin Industries, Ltd.; KYNAR (registered trademark) series and KYNAR FLEX (registered trademark) series manufactured by ALKEMA; and Dyneon FC2211 and FPO3600ULV manufactured by 3M.

[0030] [Crosslinking Agent] The crosslinking agent is not particularly limited as long as it can undergo a crosslinking reaction with the above-mentioned crosslinkable resin, and examples thereof include isocyanurates such as triallyl isocyanurate (for example, TAIC (registered trademark) manufactured by Mitsubishi Chemical Corporation); cyanurates such as triallyl cyanurate; maleimides such as N,N'-m-phenylenedimaleimide; allyl esters of polyvalent acids such as diallyl phthalate, diallyl isophthalate, diallyl maleate, diallyl fumarate, diallyl sebacate, and triallyl phosphate; diethylene glycol bisallyl carbonate; allyl ethers such as ethylene glycol diallyl ether, triallyl ether of trimethylolpropane, and partial allyl ether of pentaerythritol; allyl-modified resins such as allylated novolac and allylated resol resin; and trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, and other tri- to pentafunctional methacrylate and acrylate compounds. These may be used alone or in combination of two or more kinds in any ratio. Among the above, it is preferable to use triallyl isocyanurate as the crosslinking agent, because the use of triallyl isocyanurate makes it easier to react, thereby improving the sheet strength of the thermal conductive sheet.

[0031] The amount of the crosslinking agent used in the crosslinking reaction is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, even more preferably 0.3 parts by mass or more, and preferably 2.0 parts by mass or less, more preferably 1.5 parts by mass or less, and even more preferably 0.8 parts by mass or less, relative to 100 parts by mass of the crosslinkable resin. If the amount of the crosslinking agent used is equal to or more than the above lower limit, the crosslinked resin formed is sufficiently crosslinked by the crosslinking agent, thereby improving the sheet strength of the thermal conductive sheet and further increasing the resistance to tearing during use. On the other hand, if the amount of the crosslinking agent used is equal to or less than the above upper limit, the crosslinked resin formed is prevented from being excessively crosslinked by the crosslinking agent, and the flexibility of the thermal conductive sheet can be well maintained.

[0032] [Reaction initiator] The reaction initiator that can be used in the crosslinking reaction between the crosslinkable resin and the crosslinking agent is not particularly limited, and examples thereof include organic peroxides that function as radical reaction initiators, such as dibenzoyl peroxide (e.g., Niper E manufactured by Nippon Oil & Fats Co., Ltd.), t-butyl peroxyacetate, 2,2-di-(t-butylperoxy)butane, t-butyl peroxybenzoate, t-butylcumyl peroxide, dicumyl peroxide, di-t-hexyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane (e.g., Perhexa 25B-40 (registered trademark) manufactured by Nippon Oil & Fats Co., Ltd.), di-t-butyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexene-3, t-butyl hydroperoxide, t-butyl peroxyisobutyrate, lauroyl peroxide, dipropionyl peroxide, and p-menthane hydroperoxide. These may be used alone or in combination of two or more kinds in any desired ratio. For example, by using a reaction initiator in the crosslinking reaction, radicals are generated, which allows the crosslinking reaction to start smoothly. Among the above, it is preferable to use dibenzoyl peroxide as the reaction initiator. If dibenzoyl peroxide is used, the crosslinking reaction can be carried out well at a low temperature (for example, 150°C or less), so that the amount of gas generated is reduced and the number of micropores formed in the thermal conductive sheet can be reduced, so that the thermal conductive sheet can be made more resistant to tearing during use.

[0033] The amount of the reaction initiator used in the crosslinking reaction is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, even more preferably 0.3 parts by mass or more, and preferably 2.0 parts by mass or less, more preferably 1.5 parts by mass or less, and even more preferably 0.8 parts by mass or less, relative to 100 parts by mass of the crosslinkable resin. If the amount of the reaction initiator used is equal to or more than the lower limit, the crosslinked resin formed is sufficiently crosslinked by the crosslinking agent, improving the sheet strength of the thermal conductive sheet and further increasing the resistance to tearing during use. On the other hand, if the amount of the reaction initiator used is equal to or less than the upper limit, the amount of gas generated during the crosslinking reaction can be reduced, thereby reducing the number of micropores formed in the thermal conductive sheet, and thus the resistance to tearing during use of the thermal conductive sheet can be further increased.

[0034] The mass ratio of the amount of the crosslinking agent used to the amount of the reaction initiator used in the crosslinking reaction (crosslinking agent / reaction initiator) can be 1 / 3 or more and 3 / 1 or less.

[0035] [Method of forming crosslinked resin] The crosslinked resin can be formed by heating the above-mentioned crosslinkable resin, the crosslinking agent, and an optional reaction initiator to cause a crosslinking reaction. The conditions for the crosslinking reaction, such as the heating temperature and heating time, will be described later in the section "Method for manufacturing the thermal conductive sheet."

[0036] [Ratio of crosslinked resin content] The proportion of the cross-linked resin in the resin contained in the thermal conductive sheet is preferably 30% by mass or more, more preferably 40% by mass or more, even more preferably 50% by mass or more, even more preferably more than 70% by mass, even more preferably 85% by mass or more, and particularly preferably 100% by mass. If the proportion of the cross-linked resin in the resin is 30% by mass or more, the sheet strength of the thermal conductive sheet can be improved, and the resistance to tearing during use can be further increased. The proportion of the crosslinked resin in the resin contained in the thermal conductive sheet may be 70% by mass or less, or may be 60% by mass or less. The amount of cross-linked resin contained in the thermal conductive sheet is usually equal to the amount of cross-linkable resin used in the manufacture of the thermal conductive sheet. Therefore, the ratio of cross-linked resin in the resin contained in the thermal conductive sheet is usually equal to the ratio of cross-linkable resin in the resin (including cross-linkable resin and resin other than cross-linkable resin) used in the manufacture of the thermal conductive sheet.

[0037] <<Other resins>> The resin contained in the thermal conductive sheet of the present invention may contain resins other than the above-mentioned crosslinked resins (hereinafter, sometimes referred to as "other resins"). Here, the other resin is a resin that is not crosslinked (non-crosslinked resin). In addition, as the other resin, a resin that does not undergo a crosslinking reaction with the above-mentioned crosslinking agent (also referred to as a "non-crosslinkable resin") can be used. For example, as the other resin, a resin that does not undergo a peroxide crosslinking reaction with the crosslinking agent can be used. As the other resin, it is preferable to use a resin that is liquid at room temperature and normal pressure. By using a resin that is liquid at room temperature and normal pressure in addition to a crosslinked resin that is normally solid at room temperature and normal pressure, the flexibility of the thermal conductive sheet can be increased.

[0038] [Resin that is liquid at room temperature and pressure] The resin that is liquid at room temperature and normal pressure is a component that can impart flexibility to the thermal conductive sheet. As the resin that is liquid at room temperature and normal pressure, for example, a thermoplastic resin that is liquid at room temperature and normal pressure can be used.

[0039] - Thermoplastic fluororesin that is liquid at room temperature and pressure - Because the thermally conductive sheet contains a thermoplastic resin that is liquid at room temperature and normal pressure, the flexibility of the thermally conductive sheet can be improved, and for example, the adhesion between the thermally conductive sheet and the adherend (heat generating body, heat dissipating body) to which the thermally conductive sheet is adhered can be increased, allowing the thermally conductive sheet to exhibit high thermal conductivity.

[0040] Examples of thermoplastic resins that are liquid at room temperature and normal pressure include acrylic resins, epoxy resins, silicone resins, fluororesins, etc. These may be used alone or in combination of two or more in any ratio. Among these, thermoplastic fluororesins that are liquid at room temperature and pressure are preferred, since they not only improve the flame retardancy, heat resistance, oil resistance, and chemical resistance of the thermal conductive sheet, but also increase interfacial adhesion and reduce interfacial thermal resistance even under relatively low pressure, thereby improving the thermal conductivity (i.e., heat dissipation characteristics) of the thermal conductive sheet.

[0041] The thermoplastic fluororesin that is liquid at room temperature and normal pressure is not particularly limited as long as it is a thermoplastic fluororesin that is liquid at room temperature and normal pressure. Examples of the thermoplastic fluororesin that is liquid at room temperature and normal pressure include vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropentene-tetrafluoroethylene ternary copolymer, perfluoropropene oxide polymer, tetrafluoroethylene-propylene-vinylidene fluoride copolymer, etc. These may be used alone or in combination of two or more at any ratio. In addition, examples of commercially available thermoplastic fluororesins that are liquid at room temperature and normal pressure include Viton (registered trademark) LM manufactured by DuPont Co., Ltd., Daiel (registered trademark) G-101 manufactured by Daikin Industries, Ltd., Dyneon FC2210 manufactured by 3M Ltd., and the SIFEL series manufactured by Shin-Etsu Chemical Co., Ltd.

[0042] The viscosity of the thermoplastic fluororesin that is liquid at room temperature and normal pressure is not particularly limited, but in terms of good kneadability, fluidity, and crosslinking reactivity and excellent moldability, the viscosity (viscosity coefficient) at a temperature of 80°C is preferably 500 cP or more and 30,000 cP or less, and more preferably 550 cP or more and 25,000 cP or less.

[0043] [Content of other resins] The ratio of other resins (non-crosslinked resins) in the resin contained in the thermal conductive sheet is preferably 70% by mass or less, more preferably 50% by mass or less, even more preferably 30% by mass or less, and particularly preferably 0% by mass. If the ratio of other resins in the resin is equal to or less than the above-mentioned predetermined value, the content of crosslinked resin in the thermal conductive sheet can be increased to improve the sheet strength and further increase the resistance to tearing during use. The ratio of the other resins in the resin contained in the thermal conductive sheet can be 30% by mass or more, and can also be 40% by mass or more. In addition, the proportion of other resins in the resin contained in the thermal conductive sheet is usually the same as the proportion of resins other than the crosslinkable resin (non-crosslinkable resin) in the resin (resin including crosslinkable resin and resin other than crosslinkable resin) used in the production of the thermal conductive sheet.

[0044] <Particulate filler> The particulate filler is not particularly limited, and examples thereof include alumina particles, zinc oxide particles, boron nitride particles, aluminum nitride particles, silicon nitride particles, silicon carbide particles, magnesium oxide particles, and particulate carbon materials. These particulate fillers may be used alone or in combination of two or more kinds in any desired ratio.

[0045] From the viewpoint of increasing the thermal conductivity of the produced thermally conductive sheet, it is preferable to use a particulate carbon material as the particulate filler.

[0046] <<Carbon particles>> The particulate carbon material is not particularly limited, and examples thereof include artificial graphite, flaky graphite, exfoliated graphite, natural graphite, acid-treated graphite, negative electrode active material, expandable graphite, expanded graphite, and other graphites; carbon black; etc. These may be used alone or in combination of two or more.

[0047] Among the above, it is preferable to use expanded graphite as the particulate carbon material. By using expanded graphite, the thermal conductivity of the thermal conductive sheet can be further improved. Here, the expanded graphite can be obtained by, for example, chemically treating graphite such as flake graphite with sulfuric acid or the like to obtain expandable graphite, expanding the same by heat treatment, and then pulverizing the same. Examples of the expanded graphite include EC1500, EC1000, EC500, EC300, EC100, and EC50 (all trade names) manufactured by Ito Graphite Industries Co., Ltd.

[0048] <<Properties of particulate filler>> The volume average particle diameter of the particulate filler is preferably 10 μm or more, preferably 20 μm or more, more preferably 30 μm or more, even more preferably 40 μm or more, preferably 180 μm or less, more preferably 160 μm or less, and even more preferably 140 μm or less. If the volume average particle diameter of the particulate filler is equal to or greater than the above lower limit, it is presumed that the heat transfer path of the particulate filler in the heat conductive sheet can be well formed, and the heat conductivity of the heat conductive sheet can be improved. On the other hand, if the volume average particle diameter of the particulate filler is equal to or less than the above upper limit, the thickness precision of the heat conductive sheet can be sufficiently high. In addition, if the volume average particle diameter of the particulate filler is within the above-mentioned predetermined range, the resistance to tearing during use of the heat conductive sheet can be further improved. In the present invention, the "volume average particle size" can be measured in accordance with JIS Z8825, and refers to the particle size at which the cumulative volume calculated from the small diameter side is 50% in the particle size distribution (volume basis) measured by a laser diffraction method.

[0049] The particulate filler preferably has an aspect ratio (major axis / minor axis) of more than 1 and not more than 10, more preferably more than 1 and not more than 5. If the particulate filler has an aspect ratio of more than 1 and not more than 10, it is presumed that the particulate filler is easily oriented well in the thickness direction in the thermal conductive sheet, and the thermal conductivity of the thermal conductive sheet in the thickness direction can be increased. In the present invention, the "aspect ratio" can be determined by observing the particulate filler with a SEM (scanning electron microscope), measuring the maximum diameter (long diameter) and the particle diameter (short diameter) in a direction perpendicular to the maximum diameter for any 50 particulate fillers, and calculating the average ratio of the long diameter to the short diameter (long diameter / short diameter). In the above, for example, when the particulate filler is scaly, the "long diameter" refers to the length in the direction of the long axis of the main surface of the scaly shape, and the "short diameter" refers to the length in the direction perpendicular to the long axis of the main surface.

[0050] <<Particulate filler content>> The content of the particulate filler in the thermal conductive sheet is preferably 20 parts by mass or more, more preferably 30 parts by mass or more, even more preferably 40 parts by mass or more, even more preferably 50 parts by mass or more, and particularly preferably 55 parts by mass or more, and is preferably 200 parts by mass or less, more preferably 150 parts by mass or less, even more preferably 100 parts by mass or less, and even more preferably 80 parts by mass or less, relative to 100 parts by mass of the resin. If the content of the particulate filler in the thermal conductive sheet is equal to or more than the above lower limit, the generated gas is efficiently discharged through the surface or inside of the particulate filler during the crosslinking reaction step in the manufacturing method of the thermal conductive sheet described later, and the number of micropores on the surface of the thermal conductive sheet can be reduced, thereby further increasing the resistance to tearing during use of the thermal conductive sheet. In addition, if the content of the particulate filler in the thermal conductive sheet is equal to or more than the above lower limit, the thermal conductivity of the thermal conductive sheet can be improved. On the other hand, if the content of the particulate filler in the thermal conductive sheet is equal to or less than the above upper limit, the flexibility of the thermal conductive sheet can be sufficiently maintained, and as a result, the thermal resistance can be reduced. Furthermore, if the content of particulate filler in the thermal conductive sheet is below the above upper limit, the proportion of resin in the thermal conductive sheet increases and the particulate filler is well bonded to each other by the resin, making the thermal conductive sheet even more resistant to tearing during use.

[0051] <<Volume ratio of particulate filler>> The volume ratio of the particulate filler to the total volume of the resin and the particulate filler in the thermal conductive sheet is preferably 30% by volume or more, preferably 70% by volume or less, more preferably 60% by volume or less, even more preferably 50% by volume or less, and particularly preferably 40% by volume or less. If the volume ratio of the particulate filler to the total volume of the resin and the particulate filler in the thermal conductive sheet is equal to or more than the above lower limit, the generated gas is efficiently discharged through the surface or inside of the particulate filler during the crosslinking reaction process in the manufacturing method of the thermal conductive sheet described later, so that the resistance to tearing during use of the thermal conductive sheet can be further improved by reducing the number of micropores on the surface of the thermal conductive sheet. In addition, if the volume ratio of the particulate filler to the total volume of the resin and the particulate filler in the thermal conductive sheet is equal to or more than the above lower limit, the thermal conductivity of the thermal conductive sheet can be improved. On the other hand, if the volume ratio of the particulate filler to the total volume of the resin and the particulate filler in the thermal conductive sheet is equal to or less than the above upper limit, the flexibility of the thermal conductive sheet can be sufficiently maintained, and as a result, the thermal resistance can be reduced. Furthermore, if the proportion of the volume of the particulate filler in the total volume of the resin and particulate filler in the thermal conductive sheet is below the above upper limit, the proportion of resin in the thermal conductive sheet increases and the particulate filler is well bonded to each other by the resin, making the thermal conductive sheet even more resistant to tearing during use. The proportion of the volume of the particulate filler in the total volume of the resin and the particulate filler in the thermally conductive sheet may be 35% by volume or more, or 40% by volume or more. In the above "total volume of the resin and particulate filler in the thermal conductive sheet," the volume of the crosslinked resin contained in the resin usually coincides with the volume of the crosslinkable resin used in the manufacture of the thermal conductive sheet. Therefore, the above "total volume of the resin and particulate filler in the thermal conductive sheet" usually coincides with the total volume of the resin (including the crosslinkable resin and the resin other than the crosslinkable resin) and the particulate filler used in the manufacture of the thermal conductive sheet.

[0052] <Other ingredients> The thermally conductive sheet of the present invention may further contain optional components other than the above-mentioned resin and particulate filler (hereinafter, sometimes referred to as "other components"). The other components are not particularly limited as long as they are components that can be used in the manufacture of a thermally conductive sheet, and examples thereof include fibrous carbon materials; flame retardants such as red phosphorus flame retardants and phosphate ester flame retardants; plasticizers such as fatty acid ester plasticizers; toughness improvers such as urethane acrylate; moisture absorbents such as calcium oxide and magnesium oxide; adhesion improvers such as silane coupling agents, titanium coupling agents, and acid anhydrides; wettability improvers such as nonionic surfactants and fluorine surfactants; ion trapping agents such as inorganic ion exchangers; and the like.

[0053] <<Dispersant>> The heat conductive sheet of the present invention may further contain a dispersant as another component. By using the dispersant, the particulate filler and the like can be well dispersed in the heat conductive sheet. In addition, by using the dispersant, the particulate filler in the sheet can be uniformly dispersed, thereby increasing the flexibility of the heat conductive sheet, and the gas generated during the crosslinking reaction process of the heat conductive sheet manufacturing method described later can be efficiently discharged to the outside, thereby reducing the number of micropores formed in the heat conductive sheet. The dispersant is a component different from the above-mentioned resin.

[0054] Here, the dispersant is not particularly limited as long as the desired effect of the present invention is obtained, but from the viewpoint of further dispersing the particulate filler, etc. in the thermal conductive sheet and further reducing the number of micropores formed in the thermal conductive sheet, it is preferable to use a polymer, and it is more preferable to use a polymer having an amine value (e.g., a basic group-containing polymer, etc.).

[0055] From the viewpoint of dispersing the particulate filler and the like in the thermally conductive sheet more satisfactorily and further reducing the number of micropores formed in the thermally conductive sheet, it is preferable that the dispersant has an amine value. The amine value of the dispersant is preferably 5 mgKOH / g or more, more preferably 10 mgKOH / g or more, and is preferably 50 mgKOH / g or less, and more preferably 20 mgKOH / g or less. If the amine value of the dispersant is within the above-mentioned range, the particulate filler and the like can be more effectively dispersed in the thermal conductive sheet, and the number of micropores formed in the thermal conductive sheet can be further reduced. In the present invention, the amine value of the dispersant can be measured by titration with potassium hydroxide (KOH).

[0056] From the viewpoint of dispersing the particulate filler and the like in the thermally conductive sheet more satisfactorily and further reducing the number of micropores formed in the thermally conductive sheet, it is preferable that the dispersant has an acid value. The acid value of the dispersant is preferably 3 mgKOH / g or more, more preferably 5 mgKOH / g or more, and is preferably 80 mgKOH / g or less, and more preferably 50 mgKOH / g or less. If the acid value of the dispersant is within the above-mentioned range, the produced thermal conductive sheet can be made more resistant to tearing during use. In the present invention, the acid value of the dispersant can be measured by titration with potassium hydroxide (KOH).

[0057] As the dispersant, commercially available products can also be used, and for example, "Ajisper 821B" (manufactured by Ajinomoto Fine-Techno Co., Ltd.) and "BYK-2013" (manufactured by BYK-Chemie) can be suitably used.

[0058] [Dispersant Content] The content of the dispersant in the thermally conductive sheet can be, for example, not less than 0 parts by mass and not more than 10 parts by mass with respect to 100 parts by mass of the resin. The content of the dispersant in the thermally conductive sheet can be, for example, not less than 0 parts by mass and not more than 10 parts by mass with respect to 100 parts by mass of the particulate filler.

[0059] [Mass ratio of dispersant to particulate filler] Furthermore, the mass ratio of the dispersant to the particulate filler in the thermally conductive sheet (dispersant / particulate filler) can be, for example, 0 / 100 or more, 1 / 100 or more, and 1 / 5 or less.

[0060] <Thermal Conduction Sheet Structure> The thermally conductive sheet of the present invention preferably has a structure in which the particulate filler is oriented in the thickness direction of the thermally conductive sheet. If the particulate filler is oriented in the thickness direction of the thermally conductive sheet, the thermal conductivity in the thickness direction of the thermally conductive sheet can be increased. Here, "oriented in the thickness direction of the thermal conductive sheet" refers to a state in which, when any cross section of the thermal conductive sheet is observed with a SEM (scanning electron microscope), more than half of the particulate fillers in the thermal conductive sheet have their major axes oriented at an angle of 0 to 40 degrees to the thickness direction of the sheet (parallel to the thickness direction is defined as 0 degrees).

[0061] <Thermal conductivity> The thermal conductivity of the thermal conductive sheet in the thickness direction must be 12 W / m·K or more, preferably 13 W / m·K or more, and more preferably 15 W / m·K or more. If the thermal conductivity of the thermal conductive sheet in the thickness direction is less than 12 W / m·K, the thermal conductive sheet cannot exhibit sufficient thermal conductivity in the thickness direction. On the other hand, if the thermal conductivity of the thermal conductive sheet in the thickness direction is 12 W / m·K or more, the thermal conductive sheet can exhibit sufficient thermal conductivity in the thickness direction. The upper limit of the thermal conductivity value in the thickness direction of the thermally conductive sheet is not particularly limited, but is, for example, 45 W / m·K or less. The thermal conductivity of the thermal conductive sheet in the thickness direction can be adjusted by the types and proportions of materials and components (resin, particulate filler, dispersant, etc.) contained in the thermal conductive sheet, as well as the manufacturing method and manufacturing conditions of the thermal conductive sheet.

[0062] <Sheet strength> In measuring the sheet strength of the main surface of the thermal conductive sheet, the sheet strength in the main in-plane direction Y perpendicular to the main in-plane direction X, where the sheet strength is highest, is 1.0 N / mm 2 It must be 1.3N / mm or more. 2 It is preferable that the resistance is 1.5N / mm or more. 2 More preferably, it is 1.8N / mm 2 More preferably, it is 3.0 N / mm 2 It is preferable that the resistance is less than 2.5N / mm 2 It is more preferable that the sheet strength in the main surface direction Y of the thermal conductive sheet is 1.0 N / mm 2 If the sheet strength in the main surface direction Y of the thermal conductive sheet is less than 1.0 N / mm 2 If the sheet strength in the Y direction of the main surface of the thermal conductive sheet is equal to or less than the upper limit, the thermal conductive sheet is appropriately crushed when it is sandwiched between a heat generating body and a heat dissipating body and pressurized, so that the thermal conductivity of the thermal conductive sheet can be improved.

[0063] <Asker C hardness> The Asker C hardness of the thermally conductive sheet at 70°C is preferably 50 or more, more preferably 55 or more, even more preferably 60 or more, and preferably 100 or less, more preferably 90 or less, and even more preferably 80 or less. If the Asker C hardness of the thermally conductive sheet is equal to or greater than the lower limit, the sheet strength of the thermally conductive sheet is increased, and the thermally conductive sheet is more resistant to tearing during use. On the other hand, if the Asker C hardness of the thermally conductive sheet is equal to or less than the upper limit, the thermally conductive sheet is appropriately crushed when pressed while being sandwiched between a heat generating body and a heat dissipating body, and the thermal conductivity of the thermally conductive sheet can be improved. In the present invention, the Asker C hardness of the thermally conductive sheet can be measured by the method described in the examples of this specification.

[0064] <Micropore> The surface of the thermally conductive sheet of the present invention has few micropores (also called "pinholes"). The micropores on the surface of the thermally conductive sheet are formed, for example, by gas generated in a cross-linking reaction of resin during the manufacture of the thermally conductive sheet. The micropores formed on the surface of the thermally conductive sheet can cause the thermally conductive sheet to tear when in use. In contrast, the thermally conductive sheet of the present invention has a small number of micropores formed on its surface, and is therefore less likely to tear when in use.

[0065] Specifically, the number of micropores that penetrate the thermal conductive sheet in the thickness direction and have a diameter of 48 μm to 500 μm is 2 It is necessary that the number of micropores per unit area is 200 or less, preferably 150 or less, more preferably 120 or less, even more preferably 100 or less, and even more preferably 80 or less. If the number of micropores in the thermal conductive sheet exceeds 200, the thermal conductive sheet becomes easily torn during use. On the other hand, if the number of micropores in the thermal conductive sheet is 200 or less, the thermal conductive sheet can be sufficiently prevented from being torn during use. The number of the micropores is not particularly limited, but is usually 10 or more. The number of the above-mentioned micropores in the thermal conductive sheet can be adjusted, for example, by the proportion of crosslinkable resin in the resin used in the manufacturing method of the thermal conductive sheet, the proportion of the volume of the particulate filler in the total volume of the resin and the particulate filler, and the conditions of the crosslinking reaction process (heating temperature, heating time, etc.).

[0066] <Surface roughness Sa> The surface roughness Sa of the thermal conductive sheet is preferably 2.4 μm or less, more preferably 2.2 μm or less, and even more preferably 2.0 μm or less. If the surface roughness Sa of the thermal conductive sheet is equal to or less than the above-mentioned predetermined value, the number of micropores on the surface of the thermal conductive sheet is small, making it even more difficult for the thermal conductive sheet to tear during use. Furthermore, the surface roughness Sa of the heat conductive sheet is not particularly limited, but is preferably 1.5 μm or more. Here, it is preferable that the surface roughness Sa of at least one surface in the thickness direction of the thermal conductive sheet is within the above-mentioned predetermined range, and it is more preferable that the surface roughness Sa of both surfaces in the thickness direction is within the above-mentioned predetermined range.

[0067] <Thickness of thermal conductive sheet> The thickness of the thermally conductive sheet of the present invention is not particularly limited, but is preferably 200 μm or less, more preferably 150 μm or less, even more preferably 100 μm or less, preferably 50 μm or more, more preferably 60 μm or more, and more preferably 70 μm or more. If the thickness of the thermally conductive sheet is equal to or less than the upper limit, the thermal conductivity of the thermally conductive sheet in the thickness direction can be increased. On the other hand, if the thickness of the thermally conductive sheet is equal to or more than the lower limit, the thermally conductive sheet does not become too thin, so that the resistance to tearing, flame retardancy, strength, and handleability of the thermally conductive sheet during use can be sufficiently ensured.

[0068] (Method of manufacturing thermal conductive sheet) The method for producing the thermally conductive sheet of the present invention includes the steps of (A) pressing a composition containing a resin containing a crosslinkable resin, a particulate filler, and a crosslinking agent into a sheet to obtain a pre-thermally conductive sheet, (B) stacking a plurality of pre-thermally conductive sheets in the thickness direction or folding or rolling the pre-thermally conductive sheet to obtain a laminate, (C) heating the laminate while pressing it in the stacking direction to perform a crosslinking reaction, and (D) slicing the laminate at an angle of 45° or less with respect to the stacking direction to obtain a thermally conductive sheet. The thermally conductive sheet of the present invention may further include any steps other than the steps (A) to (D) described above.

[0069] The method for producing a thermally conductive sheet of the present invention must satisfy at least one of the following requirements (1) to (3). (1) The content of the crosslinkable resin in the resin is 70 mass % or less. (2) The volume ratio of the particulate filler to the total volume of the resin and the particulate filler is 30 volume percent or more. (3) The heating temperature in the crosslinking reaction process is 150°C or lower.

[0070] Here, in the method for producing a thermal conductive sheet of the present invention, (1) when the content of cross-linkable resin in the resin is 70 mass% or less, the amount of gas generated in the cross-linking reaction process can be reduced, thereby reducing the number of micropores (pinholes) formed in the produced thermal conductive sheet, making the thermal conductive sheet less likely to tear during use.

[0071] In addition, in the thermal conductive sheet manufacturing method of the present invention, (2) when the volume ratio of the particulate filler to the total volume of the resin and the particulate filler is 30 volume % or more, the gas generated in the crosslinking reaction process can be efficiently discharged through the surface or inside of the particulate filler, thereby reducing the number of micropores (pinholes) formed in the thermal conductive sheet manufactured, making the thermal conductive sheet less likely to tear during use.

[0072] Furthermore, in the method for producing a thermal conductive sheet of the present invention, (3) when the heating temperature in the crosslinking reaction process is 150°C or less, the amount of gas generated in the crosslinking reaction process can be reduced, thereby reducing the number of micropores (pinholes) formed in the produced thermal conductive sheet, making the thermal conductive sheet less likely to tear during use.

[0073] Therefore, the method for producing a thermally conductive sheet of the present invention can produce a thermally conductive sheet that is not easily torn during use by satisfying at least one of the above (1) to (3).

[0074] The method for manufacturing a thermally conductive sheet of the present invention may satisfy only one of the above (1) to (3), may satisfy only two of the above (1) to (3), or may satisfy all of the above (1) to (3). Furthermore, from the viewpoint of further increasing the resistance of the produced thermal conductive sheet to tearing during use, it is preferable that at least (3) is satisfied, and it is particularly preferable that (1) is not satisfied, and only (2) and (3) are satisfied.

[0075] From the viewpoint of increasing the resistance of the produced thermally conductive sheet to tearing during use, it is particularly preferable that the thermally conductive sheet does not satisfy (1) and satisfies only (2) and (3), for the following reasons. First, when (1) is not satisfied, the number of micropores generated increases slightly compared to when (1) is satisfied, but since (2) and (3) are satisfied, the number of micropores formed in the manufactured thermal conductive sheet can be sufficiently reduced. Furthermore, since (1) is not satisfied (i.e., the content of cross-linkable resin in the resin exceeds 70 mass%), the content of cross-linkable resin in the resin contained in the manufactured thermal conductive sheet increases, and the sheet strength of the thermal conductive sheet is improved. In this way, the number of micropores in the manufactured thermal conductive sheet can be reduced and the sheet strength of the thermal conductive sheet can be improved, so that the thermal conductive sheet is particularly resistant to tearing during use.

[0076] According to the method for producing a thermally conductive sheet of the present invention, the above-mentioned thermally conductive sheet of the present invention can be produced efficiently.

[0077] <(A) Pre-heat conductive sheet molding process> In the pre-thermal conductive sheet molding step, a composition containing a resin containing a crosslinkable resin, a particulate filler, and a crosslinking agent is pressed and molded into a sheet to obtain a pre-thermal conductive sheet.

[0078] <<Composition>> The composition includes a resin containing a crosslinkable resin, a particulate filler, and a crosslinking agent. The composition may further include a reaction initiator. Furthermore, the composition may further include components (other components) other than the above-mentioned resin, particulate filler, crosslinking agent, and reaction initiator.

[0079] 〔resin〕 Here, the resin contained in the composition contains a crosslinkable resin, and optionally contains a resin other than the crosslinkable resin (non-crosslinkable resin). As the crosslinkable resin, for example, the crosslinkable resin that can be used to form the crosslinked resin described above in the section "Thermal Conductive Sheet" can be used. In addition, as the resin other than the crosslinkable resin (non-crosslinkable resin), for example, the resin other than the crosslinkable resin (other resin) that can be included in the resin described above in the section "Thermal Conductive Sheet" can be used.

[0080] When the method for producing a thermal conductive sheet of the present invention satisfies the above (1), the content of the crosslinkable resin in the resin contained in the composition must be 70% by mass or less, preferably 60% by mass or less, preferably 30% by mass or more, more preferably 40% by mass or more, and even more preferably 50% by mass or more. When the content of the crosslinkable resin in the resin is 70% by mass or less, the amount of gas generated in the crosslinking reaction step can be reduced, thereby reducing the number of micropores (pinholes) formed in the produced thermal conductive sheet, making the thermal conductive sheet less likely to tear during use. On the other hand, when the content of the crosslinkable resin in the resin is 30% by mass or more, the sheet strength of the produced thermal conductive sheet can be improved, and the resistance to tearing during use can be further increased.

[0081] However, when the method for producing a thermal conductive sheet of the present invention does not satisfy (1) but satisfies (2) and (3), the content of the crosslinkable resin in the resin contained in the composition is more than 70 mass%, preferably 85 mass% or more, and particularly preferably 100 mass%. If the content of the crosslinkable resin in the resin is more than 70 mass%, the sheet strength of the produced thermal conductive sheet can be improved, and the resistance to tearing during use can be further increased.

[0082] [Particulate filler] As the particulate filler, for example, the particulate filler described above in the section "Thermal Conduction Sheet" can be used.

[0083] Here, the volume ratio of the particulate filler to the total volume of the resin and the particulate filler in the composition must be 30% by volume or more, preferably 70% by volume or less, more preferably 60% by volume or less, even more preferably 50% by volume or less, and particularly preferably 40% by volume or less. If the volume ratio of the particulate filler to the total volume of the resin and the particulate filler in the composition is 30% by volume or more, the gas generated during the crosslinking reaction process described below is efficiently discharged through the surface or inside of the particulate filler, so that the number of micropores on the surface of the thermal conductive sheet produced can be reduced, making the thermal conductive sheet less likely to tear during use. In addition, if the volume ratio of the particulate filler to the total volume of the resin and the particulate filler in the composition is 30% by volume or more, the thermal conductivity of the thermal conductive sheet produced can be increased. On the other hand, if the volume ratio of the particulate filler to the total volume of the resin and the particulate filler in the composition is the above upper limit or less, the flexibility of the thermal conductive sheet produced can be sufficiently maintained, and as a result, the thermal resistance can be reduced. Furthermore, if the proportion of the volume of the particulate filler in the total volume of the resin and particulate filler in the composition is below the above upper limit, the proportion of resin in the produced thermal conductive sheet increases, and the particulate filler is well bonded to each other by the resin, making the thermal conductive sheet even more resistant to tearing during use. The proportion of the volume of the particulate filler in the total volume of the resin and the particulate filler in the composition may be 35% by volume or more, or 40% by volume or more.

[0084] The content of the particulate filler per 100 parts by mass of resin in the composition can be set within the same preferred range as the content of the particulate filler per 100 parts by mass of resin in the thermal conductive sheet described above in the "Thermal Conductive Sheet" section.

[0085] [Crosslinking Agent] As the crosslinking agent, the crosslinking agents that can be used to form the crosslinked resin described above in the section "Thermal Conductive Sheet" can be used.

[0086] The content of the crosslinking agent per 100 parts by mass of the crosslinkable resin in the composition can be set within the same range as the preferred range of the amount of crosslinking agent used per 100 parts by mass of the crosslinkable resin described above in the section "Thermal Conductive Sheet."

[0087] [Reaction initiator] As the reaction initiator, any reaction initiator that can be used in the crosslinking reaction for forming the crosslinked resin described above in the section "Thermal Conductive Sheet" can be used.

[0088] The content of the reaction initiator per 100 parts by mass of the crosslinkable resin in the composition can be set within the same range as the preferred range of the amount of reaction initiator used per 100 parts by mass of the crosslinkable resin in the crosslinking reaction described above in the section "Thermal Conductive Sheet." In addition, the mass ratio of the crosslinking agent to the reaction initiator in the composition (crosslinking agent / reaction initiator) can be set, for example, within the same range as the mass ratio of the amount of crosslinking agent used to the amount of reaction initiator used in the crosslinking reaction described above in the section "Thermal Conductive Sheet."

[0089] [Other ingredients] As other components that can be contained in the composition, other components such as dispersants that can be contained in the thermally conductive sheet described above in the section "Thermal Conductive Sheet" can be used. Here, the range of the content of the dispersant per 100 parts by mass of the resin in the composition can be set, for example, within the same range as the range of the content of the dispersant per 100 parts by mass of the resin in the thermal conductive sheet described above in the section "Thermal conductive sheet." In addition, the mass ratio of the dispersant to the particulate filler in the composition (dispersant / particulate filler) can be set, for example, within the same preferred range as the mass ratio of the dispersant to the particulate filler in the thermally conductive sheet described above in the section "Thermal Conductive Sheet."

[0090] [Preparation of Composition] The composition is not particularly limited and can be prepared by mixing the above-mentioned components. The mixing of the above-mentioned components can be carried out using known mixing devices such as kneaders, mixers such as Henschel mixers, Hobart mixers, and high-speed mixers, twin-screw kneaders, and rolls, without any particular limitations. The mixing may be carried out in the presence of a solvent such as ethyl acetate. The resin may be dissolved or dispersed in a solvent in advance to form a resin solution, which may then be mixed with the particulate filler and crosslinking agent, as well as an optionally added reaction initiator and other components. The mixing time may be, for example, 5 minutes or more and 60 minutes or less. The mixing temperature may be, for example, 5°C or more and 150°C or less.

[0091] <<Molding of the composition>> The composition prepared as described above can be optionally degassed and crushed, and then pressed to form into a sheet. The sheet-shaped composition thus pressurized can be used as a pre-heat conductive sheet. If a solvent is used during mixing, it is preferable to remove the solvent before forming into a sheet. For example, if degassing is performed using vacuum degassing, the solvent can be removed at the same time as degassing.

[0092] Here, the composition can be molded into a sheet using a known molding method such as press molding, rolling molding, or extrusion molding, without any particular limitation, as long as the molding method is one in which pressure is applied. Among them, the composition is preferably molded into a sheet by rolling molding (primary processing), and more preferably molded into a sheet by passing the composition between rolls while sandwiched between protective films. The protective film is not particularly limited, and may be a polyethylene terephthalate (PET) film or the like that has been subjected to sandblasting. The roll temperature may be 5°C or higher and 150°C or lower, the roll gap may be 50 μm or higher and 2500 μm or lower, the roll linear pressure may be 1 kg / cm or higher and 3000 kg / cm or lower, and the roll speed may be 0.1 m / min or higher and 20 m / min or lower.

[0093] <<Pre-heat conductive sheet>> Furthermore, in the pre-thermal conductive sheet formed by pressing the composition into a sheet, the particulate filler is presumably oriented primarily in the in-plane direction, thereby improving the thermal conductivity of the pre-thermal conductive sheet in the in-plane direction in particular.

[0094] <(B) Laminate formation process> In the laminate formation step, a laminate is obtained in which a plurality of pre-thermally conductive sheets obtained in the pre-thermally conductive sheet forming step are laminated in the thickness direction, or the pre-thermally conductive sheet is folded or rolled to obtain a laminate in which a plurality of thermally conductive sheets containing a resin and a particulate filler are formed in the thickness direction. Here, the formation of the laminate by folding the pre-thermally conductive sheet is not particularly limited, and can be performed by folding the pre-thermally conductive sheet at a constant width using a folding machine. In addition, the formation of the laminate by rolling the pre-thermally conductive sheet is not particularly limited, and can be performed by rolling the pre-thermally conductive sheet around an axis parallel to the short side or long side of the pre-thermally conductive sheet. In addition, the formation of the laminate by stacking the pre-thermally conductive sheets is not particularly limited, and can be performed using a lamination device. For example, if a sheet lamination device (manufactured by Nikkiso Co., Ltd., product name "Hi-Stacker") is used, it is possible to suppress the intrusion of air between the layers, so that a good laminate can be efficiently obtained.

[0095] In the lamination step, it is preferable to pressurize the obtained laminate in the lamination direction (secondary pressurization) while heating at a temperature lower than the heating temperature in the crosslinking reaction step described later. By performing the secondary pressurization in which the laminate is pressed in the lamination direction while heating at a temperature lower than the heating temperature in the crosslinking reaction step described later, and then performing the crosslinking reaction step described later, the crosslinking reaction can be performed in a state in which fusion between the laminated pre-thermal conductive sheets is promoted, and therefore the crosslinking strength between the interfaces of each layer in the laminate can be improved.

[0096] Here, the pressure applied to the laminate in the stacking direction can be 0.01 MPa or more, preferably 0.03 MPa or more, and more preferably 0.05 MPa or more, and can be 0.50 MPa or less, preferably 0.30 MPa or less, and more preferably 0.10 MPa or less.

[0097] Furthermore, the heating temperature of the laminate is not particularly limited as long as it is lower than the heating temperature in the crosslinking reaction step described below, but can be less than 90°C, preferably 85°C or less, and more preferably 80°C or less, and can be 30°C or more, preferably 40°C or more, and more preferably 50°C or more. Furthermore, the heating time for the laminate can be, for example, 30 seconds or more and 5 minutes or less.

[0098] In addition, in a laminate obtained by stacking, folding or rolling the pre-thermal conductive sheet, it is presumed that the particulate filler is oriented in a direction approximately perpendicular to the stacking direction.

[0099] <(C) Crosslinking reaction step> In the crosslinking reaction step, the laminate is heated while being pressurized in the lamination direction to cause a crosslinking reaction, whereby the crosslinkable resin and the crosslinked body are crosslinked to form a crosslinked resin, improving the sheet strength of the produced thermal conductive sheet and making it less likely to tear during use.

[0100] Here, the pressure when the laminate is pressed in the stacking direction in the crosslinking reaction is preferably 0.01 MPa or more, more preferably 0.02 MPa or more, even more preferably 0.03 MPa or more, preferably 0.5 MPa or less, more preferably 0.1 MPa or less, and even more preferably 0.05 MPa or less. If the pressure when the laminate is pressed in the stacking direction is equal to or higher than the above lower limit, the sheet strength in the main in-plane direction Y of the produced thermal conductive sheet can be improved, thereby further increasing the resistance of the thermal conductive sheet to tearing during use. On the other hand, if the pressure when the laminate is pressed in the stacking direction is equal to or lower than the above upper limit, the laminate can be prevented from being excessively crushed.

[0101] In addition, examples of the method of applying pressure include applying pressure to only the two upper and lower surfaces in the stacking direction of the laminate, or to all four surfaces of the laminate including at least the two upper and lower surfaces in the stacking direction of the laminate. From the viewpoint of allowing gas generated during the crosslinking reaction to escape, it is preferable to apply pressure to only the two upper and lower surfaces in the stacking direction of the laminate.

[0102] The heating temperature in the crosslinking reaction step must or preferably be 150°C or less, more preferably 140°C or less, even more preferably 120°C or less, even more preferably 110°C or less, preferably 90°C or more, more preferably 92°C or more, and even more preferably 95°C or more. If the heating temperature in the crosslinking reaction step is 150°C or less, the amount of gas generated in the crosslinking reaction step can be reduced, thereby reducing the number of micropores (pinholes) formed in the thermal conductive sheet produced, making the thermal conductive sheet less likely to tear during use. On the other hand, if the heating temperature in the crosslinking reaction step is 90°C or more, the crosslinking reaction can be carried out well, improving the sheet strength of the thermal conductive sheet produced, and further increasing the resistance to tearing during use.

[0103] In addition, the heating time in the crosslinking reaction step is preferably 1 hour or more, more preferably 3 hours or more, even more preferably 5 hours or more, and preferably 24 hours or less, more preferably 12 hours or less, and even more preferably 8 hours or less. If the heating time in the crosslinking reaction step is equal to or more than the lower limit, the crosslinking reaction is carried out well, improving the sheet strength of the produced thermal conductive sheet and making it more difficult to tear during use. On the other hand, if the heating time in the crosslinking reaction step is equal to or less than the upper limit, the crosslinking reaction is prevented from proceeding excessively, and the flexibility of the thermal conductive sheet can be maintained well.

[0104] <(D) Slicing process> In the slicing step, the laminate cross-linked in the cross-linking step is sliced ​​at an angle of 45° or less with respect to the lamination direction to obtain a thermally conductive sheet consisting of slices of the laminate. The method for slicing the laminate is not particularly limited, and examples thereof include a multi-blade method, a laser processing method, a water jet method, and a knife processing method. Among these, the knife processing method is preferred because it is easy to make the thickness of the thermally conductive sheet uniform. In addition, the cutting tool used for slicing the laminate is not particularly limited, and a slicing member having a smooth plate surface with slits and a blade portion protruding from the slit portion (for example, a plane or slicer with a sharp blade) can be used.

[0105] From the viewpoint of increasing the thermal conductivity of the thermal conduction sheet, the angle at which the laminate is sliced ​​is preferably 30° or less with respect to the stacking direction, more preferably 15° or less with respect to the stacking direction, and preferably approximately 0° with respect to the stacking direction (i.e., in the direction along the stacking direction).

[0106] In the thermally conductive sheet thus obtained, the particulate filler is well oriented in the thickness direction, and the thermal conductivity in the thickness direction is excellent.

[0107] In addition, since the thermally conductive sheet manufactured by the thermally conductive sheet manufacturing method of the present invention is a sheet composed of slices of a laminate, when the sheet strength of the main surface of the thermally conductive sheet is measured, the main in-plane direction X in which the sheet strength is highest usually coincides with the direction perpendicular to the stacking direction of the laminate, and therefore the main in-plane direction Y perpendicular to the main in-plane direction X usually coincides with the stacking direction of the laminate. Furthermore, since the thermally conductive sheet manufactured by the method of the present invention is a sheet composed of slices of a laminate, when the thermal conductivity of the main surface of the thermally conductive sheet is measured, the main in-plane direction X' in which the thermal conductivity is highest usually coincides with the direction perpendicular to the stacking direction of the laminate. Therefore, the main in-plane direction Y' perpendicular to the main in-plane direction X' usually coincides with the stacking direction of the laminate. Therefore, when the sheet strength of the main surface of the thermal conductive sheet is measured, the in-plane direction X in which the sheet strength is highest usually coincides with the in-plane direction X' in which the thermal conductivity of the main surface of the thermal conductive sheet is highest. And, the in-plane direction Y perpendicular to the in-plane direction X in which the sheet strength is highest usually coincides with the in-plane direction Y' perpendicular to the in-plane direction X' in which the thermal conductivity is highest. EXAMPLES

[0108] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following description, the units "%" and "parts" expressing amounts are by mass unless otherwise specified.

[0109] In each example and comparative example, (i) the Asker C hardness of the thermally conductive sheet, (ii) the sheet strength of the thermally conductive sheet, (iii) the thermal conductivity in the thickness direction of the thermally conductive sheet, (iv) the surface roughness Sa of the thermally conductive sheet, (v) the number of micropores in the thermally conductive sheet, and (vi) the resistance of the thermally conductive sheet to tearing during use were measured or evaluated using the following methods.

[0110] <(i) Asker C hardness of thermal conductive sheet> The thermally conductive sheets manufactured in each of the Examples and Comparative Examples were sliced ​​and then left at room temperature (25°C) for 10 days to prepare test specimens. These thermally conductive sheets were cut into pieces measuring 25 mm long x 50 mm wide, and stacked to a height of 9 mm to prepare blocks to prepare test specimens. Specifically, in accordance with the Asker C method of the Society of Rubber Industry, Japan (SRIS), measurements were taken using a hardness tester (manufactured by Kobunshi Keiki Co., Ltd., product name "ASKER CL-150LJ") while heating the test specimen to a temperature of 70°C on a hot plate. The height of the damper was then adjusted so that the index was between 95 and 98, and the hardness was measured five times 20 seconds after the test specimen collided with the damper, and the average value was taken as the Asker C hardness of the test specimen.

[0111] <(ii) Sheet strength of thermal conductive sheet> The thermally conductive sheets manufactured in each of the examples and comparative examples were punched out to a size of 20 mm in the X direction and 50 mm in the Y direction to prepare test pieces. A tensile test was carried out on the obtained test pieces in the Y direction at a tensile speed of 20 mm / min using a small tabletop testing machine (manufactured by Nidec-Shimpo Corporation, "FGS-500TV" and using FGP-50 as a digital force gauge) with the chuck distance being 30 mm. The maximum strength (N) during the tensile test was calculated based on the cross-sectional area of ​​the test piece (width 20 mm × thickness 0.1 mm = 2 mm 2 ) to obtain the sheet strength in the Y direction of the thermal conductive sheet (N / mm 2 ) was calculated. In the above, the "X direction" means "the in-plane direction in which the sheet strength is highest when the sheet strength is measured on the main surface of the thermal conductive sheet. Since the thermal conductive sheets manufactured in each Example and Comparative Example were made of sliced ​​pieces of the laminate, when the sheet strength was measured on the main surface of the thermal conductive sheet by the same method as described above, the "X direction" was found to be the direction perpendicular to the stacking direction of the laminate. Moreover, the "Y direction" means "a direction within the main surface perpendicular to the X direction (a direction that coincides with the stacking direction of the stacked body)".

[0112] <(iii) Thermal conductivity in the thickness direction of the thermal conductive sheet> The thermal diffusivity α (m 2 / s), specific heat at constant pressure Cp (J / g K) and specific gravity ρ (g / m 3 ) was measured by the following method. [Thermal diffusivity α(m 2 / s)] The thermal diffusivity in the thickness direction was measured using a thermal property measuring device (manufactured by Bethel Corporation, product name "Thermowave Analyzer TA35"). [Specific heat at constant pressure Cp(J / g K)] The specific heat was measured using a differential scanning calorimeter (manufactured by Rigaku, product name "DSC8230") under a temperature increase condition of 10°C / min. [Specific gravity ρ(g / m 3 )] Specific gravity (density) (g / m) was measured using an automatic specific gravity meter (manufactured by Toyo Seiki Co., Ltd., product name "DENSIMETER-H"). 3 ) was measured. The obtained measured values ​​are then used to calculate the following formula (I): λ = α × Cp × ρ (I) The thermal conductivity λ (W / m K) of the thermal conductive sheet in the thickness direction was calculated by substituting

[0113] <(iv) Surface roughness Sa of thermal conductive sheet> The surface roughness Sa of the thermally conductive sheets manufactured in each of the Examples and Comparative Examples was measured using a three-dimensional shape measuring instrument (manufactured by Keyence Corporation, product name "One Shot 3D Measuring Macroscope"). Specifically, the three-dimensional shape was measured for five analysis ranges (1cm x 1cm) extracted from the surface of the thermal conductive sheet to be evaluated. When extracting the five analysis ranges, it is desirable that each analysis range be at least 1cm apart, but if the size of the thermal conductive sheet is small, it is acceptable for the analysis ranges to overlap in part. Also, if the size of the thermal conductive sheet is small and it is not possible to ensure an analysis range of 1cm x 1cm, the analysis range may be reduced to 0.3cm x 0.3cm. Furthermore, the three-dimensional shape measurement results were filtered (2.5 mm) using software to remove waviness components, and the surface roughness Sa (μm) was automatically calculated. The average value of the five analysis points was taken as the surface roughness Sa of the thermal conductive sheet.

[0114] <(v) Number of microholes in the thermal conductive sheet> The number of microholes in the thermally conductive sheets manufactured in each of the examples and comparative examples was measured using an appearance inspection device (manufactured by Nagano Automation Co., Ltd., product name "00-6724 appearance inspection device"). Specifically, an LED light was used to illuminate the back of the thermally conductive sheet placed on a pedestal, and the entire sheet was photographed with a camera. The obtained image was binarized by image processing to identify white areas. Of these white areas, those with both a maximum diameter and a minimum diameter of 48 μm or more and 500 μm or less were determined to be microholes, and the number of such microholes was measured. From the number of microholes in the entire thermally conductive sheet obtained and the planar area of ​​the thermally conductive sheet, the planar area of ​​the thermally conductive sheet was calculated.2 The number of microholes per well was calculated.

[0115] <(vi) Difficulty in tearing the thermal conductive sheet during use> The thermally conductive sheets produced in each of the Examples and Comparative Examples were sized to 10 mm x 10 mm and placed on a first metal plate (heating element) heated to 120°C. A smooth second metal plate (heat sink) sized to 12 mm x 12 mm was placed on top of the thermal conduction sheet so that its center overlapped with the thermal conduction sheet. A cyclic test was conducted in which a pressure of 250 N was applied from above for 10 seconds and then released for 10 seconds, and this was repeated 50 times. The thermal conductive sheet was observed from directly above after the cycle test was completed, and its resistance to tearing during use was evaluated according to the following criteria, based on the extent to which the thermal conductive sheet protruded from the second metal plate. When the thermal conductive sheet was sandwiched between a heat generating body and a heat dissipating body and heated, and cycles of pressure and decompression were repeated, the thermal conductive sheet, which is prone to tearing, broke in the area where particularly strong pressure was applied, and protruded from between the heat generating body and the heat dissipating body. Therefore, the smaller the protruding area of ​​the thermal conductive sheet, the more difficult it is to tear during use, and if there is no protrusion at all, it indicates that the thermal conductive sheet is particularly difficult to tear during use. A: There is absolutely no protrusion of the thermal conductive sheet. B: The thermal conductive sheet protrudes, with at least one side being greater than 0 mm and less than 2 mm. C: The thermal conductive sheet protrudes with at least one side measuring 2 mm or more and less than 6 mm.

[0116] Example 1 <Preparation of Composition> 100 parts (56 parts by volume) of a solid fluoroelastomer (fluororubber) (manufactured by 3M Japan, trade name "Dyneon (registered trademark) FPO3600ULV", Mooney viscosity: 3.5ML1+4, 100 ° C.) and 60 parts (27 parts by volume) of expanded graphite (manufactured by Ito Graphite Industries Co., Ltd., trade name "EC300", volume average particle size: 50 μm) as a particulate filler were mixed at a temperature of 150 ° C. for 20 minutes using a pressure kneader (manufactured by Nippon Spindle). Next, after lowering the device temperature to 60 ° C., 0.5 parts of dibenzoyl peroxide (manufactured by NOF Corp., trade name "Niper E") as a reaction initiator and 0.5 parts of triallyl isocyanurate (manufactured by Nippon Kasei Co., Ltd., trade name "TAIC M60") as a crosslinking agent were mixed and kneaded for 10 minutes while maintaining the material temperature at 60 ° C. Next, the mixture obtained above was placed in a crusher (manufactured by Sansho Industry Co., Ltd., product name "Hammer Crusher HN34S") and crushed for 60 seconds to obtain a composition containing a resin, a particulate filler, a crosslinking agent, and a reaction initiator.

[0117] <Pre-heat conductive sheet forming process> Next, 50 g of the obtained composition was sandwiched between a 50 μm-thick PET film (protective film) that had been sandblasted, and roll-molded (primary pressing) under conditions of a roll gap of 550 μm, a roll temperature of 50° C., a roll linear pressure of 50 kg / cm, and a roll speed of 1 m / min to obtain a pre-heat conductive sheet with a thickness of 0.5 mm.

[0118] <Laminate formation process> Next, the obtained pre-thermal conductive sheet was cut into a size of 50 mm length × 50 mm width × 1.0 mm thickness, 55 sheets were stacked in the thickness direction of the pre-thermal conductive sheet, and further pressed in the stacking direction at a temperature of 80°C and a pressure of 0.1 MPa for 1 minute (secondary pressing) to obtain a laminate with a height of 49 mm. This secondary pressing caused the layers of the laminate to adhere more closely to each other.

[0119] <Crosslinking reaction process> Next, the obtained laminate was heated in a 100° C. atmosphere for 6 hours while a pressure of 0.03 MPa was applied from above and below with a vice, thereby causing a crosslinking reaction (vulcanization). In order to facilitate the escape of generated gases and the like, no particular force was applied to the side surfaces of the laminate.

[0120] <Slicing process> Thereafter, the entire upper surface of the obtained laminate was pressed with a metal plate, leaving a length necessary for slicing, and a pressure of 0.1 MPa was applied in the lamination direction (i.e., from above) to fix the laminate. Note that the sides and back of the laminate were not fixed. At this time, the temperature of the laminate was 25°C. Next, a cutting blade (double-edged, blade angle 2θ: 20°, maximum thickness of blade: 3.5 mm, material: carbide, Rockwell hardness: 91.5, silicon processing on blade surface: none, total length: 200 mm) was attached to the press part of a servo press (manufactured by Electric Discharge Precision Machining Laboratory), and the laminate was sliced ​​in the stacking direction (in other words, in the direction coinciding with the normal to the main surface of the stacked pre-thermal conductive sheets) at a slicing speed of 200 mm / sec and a slice width of 100 μm to obtain a thermal conductive sheet measuring 150 mm in length, 60 mm in width, and 0.10 mm in thickness. The thermally conductive sheet thus obtained was subjected to various measurements and evaluations according to the methods described above. The results are shown in Table 1.

[0121] Example 2 In preparing the composition of Example 1, the "preparation of composition", "pre-thermal conductive sheet molding process", "laminate formation process", "crosslinking reaction process" and "slicing process" were carried out in the same manner as in Example 1, except that 6 parts of a basic group-containing polymer (product name "Ajisper PB821", manufactured by Ajinomoto Fine-Techno Co., Ltd., amine value: 10 mg KOH / g, acid value: 17 mg KOH / g) was further added when mixing the resin and the particulate filler. The obtained thermally conductive sheet was then subjected to the same measurements and evaluations as in Example 1. The results are shown in Table 1.

[0122] Example 3 In preparing the composition of Example 2, when mixing the resin and the particulate filler, the amount of fluoroelastomer (manufactured by 3M Japan, product name "Dyneon (registered trademark) FPO3600ULV") that is solid at room temperature and normal pressure was reduced from 100 parts (56 parts by volume) to 50 parts (28 parts by volume), and 50 parts (28 parts by volume) of thermoplastic fluororesin (manufactured by Daikin Industries, Ltd., product name "Dai-el G-101") that is liquid at room temperature and normal pressure was further added. Except for this, the "Preparation of composition", "Pre-heat conductive sheet molding process", "Laminate formation process", "Crosslinking reaction process" and "Slicing process" were carried out in the same manner as in Example 2. The obtained thermally conductive sheet was then subjected to the same measurements and evaluations as in Example 2. The results are shown in Table 1.

[0123] Example 4 The "Preparation of composition", "Pre-heat conductive sheet molding process", "Laminate formation process", "Cross-linking reaction process" and "Slicing process" were carried out in the same manner as in Example 1, except that the "Preparation of composition" was carried out as follows. The obtained thermally conductive sheet was then subjected to the same measurements and evaluations as in Example 1. The results are shown in Table 1. <Preparation of Composition> 50 parts (28 parts by volume) of a fluoroelastomer (fluororubber) that is solid at room temperature and normal pressure (manufactured by 3M Japan, product name "Dyneon (registered trademark) FPO3600ULV", Mooney viscosity: 3.5ML1+4, 100 ° C.), 50 parts (28 parts by volume) of a thermoplastic fluororesin that is liquid at room temperature and normal pressure (manufactured by Daikin Industries, Ltd., product name "Dai-el G-101"), 90 parts (40 parts by volume) of expanded graphite (manufactured by Ito Graphite Industries Co., Ltd., product name "EC300", volume average particle size: 50 μm) as a particulate filler, and 9 parts of a basic group-containing polymer (product name "Ajisper PB821", manufactured by Ajinomoto Fine-Techno, amine value: 10 mg KOH / g, acid value: 17 mg KOH / g) were mixed at a temperature of 150 ° C. for 20 minutes using a pressure kneader (manufactured by Nippon Spindle). Next, after lowering the temperature of the device to 60°C, 0.25 parts of dibenzoyl peroxide (manufactured by NOF Corp., product name "Niper E") as a reaction initiator and 0.25 parts of triallyl isocyanurate (manufactured by Nippon Kasei Co., Ltd., product name "TAIC M60") as a crosslinking agent were mixed and kneaded for 10 minutes while maintaining the material temperature at 60°C. Next, the mixture obtained above was put into a crusher (manufactured by Sansho Industry Co., Ltd., product name "Hammer Crusher HN34S") and crushed for 60 seconds to obtain a composition containing a resin, a particulate filler, a crosslinking agent, and a reaction initiator.

[0124] Example 5 In preparing the composition of Example 4, the amount of dibenzoyl peroxide added as a reaction initiator was changed from 0.25 parts to 0.50 parts, the amount of triallyl isocyanurate added as a crosslinking agent was changed from 0.25 parts to 0.50 parts, and in the crosslinking reaction step of Example 4, the heating temperature was changed from 100°C to 150°C, and the heating time was changed from 6 hours to 1 hour. Except for this, the "preparation of composition", "pre-heat conductive sheet molding step", "laminate formation step", "crosslinking reaction step" and "slicing step" were performed in the same manner as in Example 4. The obtained thermally conductive sheet was then subjected to the same measurements and evaluations as in Example 4. The results are shown in Table 1.

[0125] Example 6 In the preparation of the composition of Example 1, when mixing the resin and the particulate filler, the amount of the fluoroelastomer (manufactured by 3M Japan, product name "Dyneon (registered trademark) FPO3600ULV") that is solid at room temperature and normal pressure was reduced from 100 parts (56 parts by volume) to 50 parts (28 parts by volume), and 50 parts (28 parts by volume) of the thermoplastic fluororesin (manufactured by Daikin Industries, Ltd., product name "Dai-el G-101") that is liquid at room temperature and normal pressure was further added. In addition, in the crosslinking reaction process of Example 1, the heating temperature was changed from 100°C to 180°C, and the heating time was changed from 6 hours to 1 hour. Except for this, the "preparation of the composition", "pre-heat conductive sheet molding process", "laminate formation process", "crosslinking reaction process" and "slicing process" were performed in the same manner as in Example 1. The obtained thermally conductive sheet was then subjected to the same measurements and evaluations as in Example 1. The results are shown in Table 1.

[0126] Comparative Example 1 In the preparation of the composition of Example 1, 50 parts (22 parts by volume) of expanded graphite (manufactured by Ito Graphite Industries Co., Ltd., product name "EC100") having a volume average particle diameter of 190 μm was used instead of 60 parts (27 parts by volume) of expanded graphite (manufactured by Ito Graphite Industries Co., Ltd., product name "EC300") having a volume average particle diameter of 50 μm, and 0.25 parts of 2,5-dimethyl-2,5-di(t-butylperoxy)hexane (manufactured by NOF Corporation, product name "Perhexa 25B-40") was used instead of 0.5 parts of dibenzoyl peroxide (manufactured by NOF Corporation, product name "Niper E") as a reaction initiator. In addition, in the crosslinking reaction step of Example 1, the heating temperature was changed from 100 ° C to 180 ° C, and the heating time was changed from 6 hours to 1 hour. Except for this, the "preparation of the composition", "pre-heat conductive sheet molding step", "laminate formation step", "crosslinking reaction step" and "slicing step" were performed in the same manner as in Example 1. The obtained thermally conductive sheet was then subjected to the same measurements and evaluations as in Example 1. The results are shown in Table 1.

[0127] [Table 1]

[0128] From Table 1, it can be seen that the thermal conductive sheets of Examples 1 to 6, which contain a resin containing a crosslinked resin and a particulate filler, have a thermal conductivity in the thickness direction that is equal to or greater than a predetermined value, and in measurement of the sheet strength of the main surface, have a sheet strength in the main plane in-direction Y perpendicular to the main plane in-direction X in which the sheet strength is highest that is equal to or greater than a predetermined value, and have a number of predetermined micropores that is equal to or less than a predetermined value, are less likely to tear during use. On the other hand, the thermal conductive sheet of Comparative Example 1, which contains a resin containing a cross-linked resin and a particulate filler, has a thermal conductivity in the thickness direction equal to or greater than a predetermined value, and has a sheet strength in a predetermined in-plane direction Y equal to or greater than a predetermined value, but has a number of predetermined micropores that exceeds a predetermined value, is found to be easily torn during use. [Industrial Applicability]

[0129] According to the present invention, it is possible to provide a thermally conductive sheet that is not easily torn during use.

Claims

1. a pre-thermal conductive sheet molding step of pressurizing a composition containing a raw material resin including a crosslinkable resin that is solid at room temperature and normal pressure and a non-crosslinkable resin that is liquid at room temperature and normal pressure, a particulate filler, and a crosslinking agent to form the composition into a sheet to obtain a pre-thermal conductive sheet; a laminate forming step of laminating a plurality of the pre-thermal conductive sheets in a thickness direction, or folding or rolling the pre-thermal conductive sheet to obtain a laminate; a crosslinking reaction step of heating the laminate while applying pressure in the lamination direction to carry out a crosslinking reaction; A slicing step of slicing the laminate at an angle of 45° or less with respect to the lamination direction to obtain a thermally conductive sheet, A method for producing a thermally conductive sheet, which satisfies at least one of the following (1) to (3): (1) The content of the crosslinkable resin in the raw material resin is 70 mass % or less. (2) The ratio of the volume of the particulate filler to the total volume of the raw resin and the particulate filler is 30 volume % or more. (3) The heating temperature in the crosslinking reaction step is 150° C. or lower.

2. The method for producing a thermal conductive sheet according to claim 1 , wherein the pressure applied to the laminate in the lamination direction in the crosslinking reaction step is 0.01 MPa or more.

3. The composition comprises a reaction initiator, The method for producing a thermal conductive sheet according to claim 1 or 2, wherein the reaction initiator includes dibenzoyl peroxide.

Citation Information

Patent Citations

  • Oscillation modulator

    JP1979023455A

  • Production of interferon

    JP1981078596A

  • Focusing mechanism of exposing optical device

    JP1986056337A

  • Heat conducting sheet, method of producing the same, and heat radiator utilizing heat conducting sheet

    JP2012038763A

  • Thermoconductive pressure-sensitive adhesive composition, thermoconductive pressure-sensitive adhesive sheet-shaped molding, production methods of them, and electronic equipment

    JP2013249446A